Technology, Training, and Touch: Finding Balance in the AI Era of Medicine - Mishra, Bibhuti Nath (Grande Medical Journal, 2025)
Medicine stands on the threshold of transformation because artificial intelligence (AI) has revolutionized how we diagnose, plan, and deliver care. Yet, the real challenge lies beyond algorithms, ensuring that innovation rather strengthens and not replaces the human bond that defines healing.